PK-PD Integration Modeling and Cutoff Value of Florfenicol against Streptococcus suis in Pigs - Lei, Zhixin; Liu, Qianying; Yang, Shuaike; Yang, Bing; Khaliq, Haseeb; Li, Kun; Ahmed, Saeed; Sajid, Abdul; Zhang, Bingzhou; Chen, Pin; Qiu, Yinsheng; Cao, Jiyue; et al. (Frontiers in Pharmacology, 2018)
The aims of the present study were to establish optimal doses and provide an alternate COPD for florfenicol against Streptococcus suis based on pharmacokinetic-pharmacodynamic integration modeling. The recommended dose (30 mg/kg.bw) were administered in healthy pigs through intramuscular and intravenous routes for pharmacokinetic studies. The main pharmacokinetic parameters of Cmax, AUC0-24h, AUC, Ke, t1/2ke, MRT, Tmax, and Clb, were estimated as 4.44 μg/ml, 88.85 μg•h/ml, 158.56 μg•h/ml, 0.048 h-1, 14.46 h, 26.11 h, 4h and 0.185 L/h•kg, respectively. The bioavailability of florfenicol was calculated to be 99.14% after I.M administration. A total of 124 Streptococcus Suis from most cities of China were isolated to determine the MIC of florfenicol. The MIC50 and MIC90 were calculated as 1 and 2 μg/ml. A serotype 2 Streptococcus suis (WH-2), with MIC value similar to MIC90, was selected as a representative for an in vitro and ex vivo pharmacodynamics study. The MIC values of WH-2 in TSB and plasma were 2 μg/ml, and the MBC/MIC ratios were 2 in TSB and plasma. The MPC was detected to be 3.2 μg/ml. According to inhibitory sigmoid Emax model, plasma AUC0-24h/MIC values of florfenicol versus Streptococcus Suis were 37.89, 44.02, and 46.42 h for the bactericidal, bacteriostatic and elimination activity, respectively. Monte Carlo simulations the optimal doses for bactericidal, bacteriostatic and elimination effects were calculated as 16.5, 19.17 and 20.14 mg/kg.bw for 50% target attainment rates (TAR), and 21.55, 25.02 and 26.85 mg/kg.bw for 90% TAR, respectively. The PK-PD cutoff value (COPD) analyzed from MCS for florfenicol against Streptococcus Suis was 1 μg/ml which could provide a sensitivity cutoff value. These results contributed an optimized alternative to clinical veterinary medicine and showed that the dose of 25.02 mg/kg florfenicol for 24 hours could have a bactericidal action against Streptococcus Suis after I.M administration. However, it should be validated in clinical practice in the future investigations.